Sulphasalazine in ankylosing spondylitis. Issue 5 (May 1986) - Feltelius, N; Hällgren, R
Abstract : In recent years sulphasalazine has gained acceptance as an effective agent for the treatment of rheumatoid arthritis. Ankylosing spondylitis is a disease where remission inducing drugs so far have been lacking. In this double blind trial sulphasalazine was compared with placebo in 37 patients with ankylosing spondylitis. Evaluation after three months' treatment showed reduction of inflammatory activity and improvement of clinical variables. The side effects were mild. The results suggest that sulphasalazine is a potentially effective and safe drug in the treatment of ankylosing spondylitis.